Some comments on Benedict's "Miao-Yao enigma": addendum - Strecker, David (2024)
I ended my paper with the words "I agree with Benedict, however, that more data on the Pa Hng languages are needed before questions such as these can be resolved." Some of these additional data have now become available. On the very day that I mailed my paper off to be considered for publication I received from Wang Pushi a comparative wordlist including 80 words in the dialect of Pa Hng spoken in Nenjie. 57 of these are new words, not given in either Mao, Meng, and Zheng or the Institute wordlist. The kindness and generosity of Professor Wang now make it possible for me to fill in some gaps and correct some mistakes in my treatment of Wenjie.